Biosynthesis in vitro of fucose-containing glycosphingolipids in human neuroblastoma IMR-32 cells. - Presper, K A (1978)
Two different glycolipid:fucosyltransferase activities involved in the biosynthesis in vitro of blood group-related glycosphingolipids have been detected in a membrane preparation isolated from a human neuroblastoma-derived clonal cell line, IMR-32. The membrane preparation contains an alpha (1,2)-fucosyltransferase (EC 2.4.1.89) that catalyzed the transfer of vucose from GDP--[14C]fucose to neolactotetraosylceramide or neolactopentaosylceramide to form types H-I and B-I glycolipids, respectively. The second fucosyltransferase catalyzes the transfer of fucose to lactotriaosylceramide [GlcNAc(beta1-3)Gal(beta1-4)Glc-Cer] to form a tetraglycosylceramide intermediate of the novel Lea-type glycolipid. UDP-galactose:lactotriaosylceramide beta-galactosyltransferase (EC 2.4.1.86) had 4 times the activity of UDP-galactose:alpha-galactosyltransferase (EC 2.4.1.87) when tested under similar conditions. alpha-Fucosyltransferase activities and the incorporation of [14C]fucose into glycoproteins and glycolipids were also compared in cells differentiated in the presence of 4 micron BrdUrd and 6-mercaptoguanosine.